Extracting DNA of nematodes communities from Argentine Pampas agricultural soils - Mondino, Eduardo Ariel; Covacevich, Fernanda; Studdert, Guillermo; Pimentel, João Pedro; Berbara, Ricardo Luiz Louro (2018)
We examined four strategies (Tris/EDTA, sodium dodecyl sulfate, Chelex 100 resin and cetyltrimethylammonium bromide -CTAB-) for extracting nucleic acid (DNA) from communities of nematodes. Nematodes were isolated from an agricultural area under different management of long-term crop rotation experiment from Argentina during three seasons. After DNA extraction, Polymerase Chain Reaction-amplifications were performed and considered as indicators of successful DNA extraction. The CTAB combined with proteinase K and phenol-chloroform-isoamyl alcohol was the unique successful method because positive amplifications were obtained by using both eukaryotic and nematode specific primers. This work could contribute to biodiversity studies of nematodes on agroecosystems.